Constructive Conflict Management: Asia-Pacific Cases (Sage, 1996)
Styles of conflict management vary across cultures. This unique volume uses cases drawn from the Asian and Pacific Island area to illustrate culture′s role in conflict mediation. The contributors focus in particular on how conflict within and between cultures can be successfully mediated on the micro-level (businesses and individuals) and how this success can be applied on the macro-level (government and organizations). The cases examined in Constructive Conflict Management cover a variety of conflict types including: regional//cultural; nuclear and extended family; environmental; and neighbourhood disputes. The book reveals that, rather than a barrier, culture can prove to be a positive resource for the mediation of